Drug Use among Street Children in Tehran, Iran: A Qualitative Study - Dejman, Masoumeh; Vameghi, Meroe; Roshanfekr, Payam; Dejman, Fatemeh; Rafiey, Hassan; Forouzan, Ameneh Setareh; Assari, Shervin; Bass, Judith; Johnson, Renee M. (Frontiers in Public Health, 2015)
Introduction and objective: Globally, children who work and live on the streets are at higher risk of undesired behavioral health outcomes, including increased drug use and abuse. Considering the rapid growth of this population in Iran and the lack of program planning that is partly due to a scarcity of research-based information, this study was conducted in 2013 to investigate drug use among street children in Tehran. Method: With a qualitative design, we conducted a Rapid Assessment and Response (RAS) Survey of street children in Tehran, 2012-2013. Data were also obtained from ten focus group discussions with street children using semi-structured questionnaires and 27 in-depth interviews with key informants in governmental, non-governmental, and international organizations. Results: The variation in age at first use, type of drugs, and pattern of drug use were found based on ethnicity. Gypsy boys and girls reported consuming more alcohol than other groups. Drug use problems were commonly described among families of street children. Children whose parents had drug-use problems described using drugs earlier than other children. Informants reported that families with drug-related problems used children for procurement of drugs. Children themselves described using drugs to cope with stress, reduce physical and psychological stressors and problems such as fatigue, sadness, and pressure resulting from frequent failures in life. Conclusion: These results suggest that intervention and prevention programs dealing with drug use of street children in Iran should include family and peers when addressing drug use by street children.